Impact of the financial strategy and the capital structure on the financial performance and competitiveness of SME-s - Gyurcsik Petronella; Дюрчік П.; Tóth Róbert; Товт Р. (ФОП Сабов А. М., 2019)
Abstract. Competitiveness – both on the macro and micro economic level – is at the centre of attention at all times; hence the particular relevance of the present study in which corporate financial strategy and corporate capital structure are examined in the context of competitiveness. The 2008 world economic crisis highlighted the importance of financial awareness and financial culture, that is, the importance of a future-oriented company management. Today those companies are able to achieve and retain a competitive position which integrate professional financial management into their operational work; thereby laying the foundations for strategic level financial management. Within and outside the company consultancy as means of expert management contribute to achieving this and also to its efficient operation.
Вплив корпоративної фінансової стратегії та структури капіталу на ефективність та конкурентоспроможність малих і середніх підприємств
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: corporate financial strategy; SME; competitiveness; capital structure